1997
DOI: 10.1161/01.atv.17.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the Apolipoprotein E Gene and Early Carotid Atherosclerosis Defined by Ultrasonography in Asymptomatic Adults

Abstract: Clinical and autoptical studies have suggested a predisposing role of the allele E4 of apolipoprotein E (apoE) in the development of atherosclerosis and cardiovascular disease. To investigate the possible contribution of apoE allele polymorphism to the carotid intima-media thickness (IMT) as assessed by ultrasound, we studied 260 asymptomatic nondiabetic subjects (121 men, 139 women; mean +/- SD age, 53 +/- 7 years), randomly selected from the population register of the inhabitants of Trieste, Italy. B-mode ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 33 publications
3
72
1
1
Order By: Relevance
“…In an earlier study, an association between the E4 allele and carotid atherosclerosis was demonstrated in middle-aged asymptomatic subjects from a general population (Cattin et al 1997). However, conflicting results have also been reported regarding the association between apoE4 and carotid atherosclerosis .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In an earlier study, an association between the E4 allele and carotid atherosclerosis was demonstrated in middle-aged asymptomatic subjects from a general population (Cattin et al 1997). However, conflicting results have also been reported regarding the association between apoE4 and carotid atherosclerosis .…”
Section: Discussionmentioning
confidence: 93%
“…Because isoforms of apolipoprotein E (apoE) have also been shown to be related to cardiovascular disease and atherosclerosis (Cattin et al 1997), we also investigated the association of apoE genotype with carotid IMT, as an independent genetic factor of the RAS.…”
Section: Introductionmentioning
confidence: 99%
“…Even after adjustment for traditional risk factors, including LDL-C levels, an association between FH gene mutations and the prevalence of CAD was found 21) . It is possible that the genes responsible for hyperlipidemia can act upon atherogenesis not only by an evident increase in the serum lipid profile but also by other gene-gene and gene-environmental interactions 22) . Although the nature of the FH molecular defect has a significant impact on the severity of hypercholesterolemia to date, there is no convincing evidence that molecular diagnosis has any important therapeutic implications.…”
Section: Discussionmentioning
confidence: 99%
“…When selecting a population for an intervention study, the genotype of individuals has been constantly ignored. Apo E genotype may in uence carotid atherosclerosis in its early stages; in particular, the E4 allele favours the disease (83,84). Consequently, in order to see protective effects against atherosclerosis, vitamin E supplementation should start as early as possible, should be maintained for longer periods, and should be associated with vitamin C. In the selection of the population to study, Apo E genotype, gender, and vitamin E status should be closely taken into consideration.…”
Section: Discussionmentioning
confidence: 99%